Somatic PIK3R1 mutations in the iSH2 domain are accessible to PI3Kα inhibition - Gabriel Morin; Alexandre P Garneau; Nabiha Bouzakher; Louise Ségot; Antoine Fraissenon; Amélie Blondel; Florence Petit; Caroline Chopinet; Franck Mayeux; Pierre Fayoux; Anne Dompmartin; Christine Bodemer; et al. (EMBO Molecular Medicine)
Abstract Mutations in PIK3R1 have recently been identified in patients with overgrowth syndromes and complex vascular malformations. PIK3R1 encodes p85α which acts as the regulatory subunit of the lipid kinase PI3Kα. PIK3R1 mutations result in the excessive activation of the AKT/mTOR pathway. Currently, there are no approved treatments specifically dedicated to patients with PIK3R1 mutations, and medical care primarily focuses on managing symptoms. In this study, we identified three patients, including two children, who had mosaic somatic PIK3R1 mutations affecting the iSH2 domain, along with severe associated symptoms that were unsuccessfully treated with rapamycin. We conducted in vitro experiments to investigate the impact of these mutations, including a double PIK3R1 mutation in cis observed in one patient. Our findings revealed that p85α mutants in the iSH2 domain showed sensitivity to alpelisib, a pharmacological inhibitor of PI3Kα. Based on these findings, we received authorization to administer alpelisib to all three patients. Following drug introduction, patients rapidly demonstrated clinical improvement, pain, fatigue and inflammatory flares were attenuated. Magnetic Resonance Imaging showed a mean decrease of 22.67% in the volume of vascular malformations over twelve months of treatment with alpelisib. No drug-related adverse events were reported during the course of the study. In conclusion, this study provides support for the use of PI3Kα inhibition as a promising therapeutic approach for individuals with PIK3R1-related anomalies.